Investigation into the Professional Culture of a Foreign Language Teacher in a Multicultural Classroom from Faculty and International Students' Perspectives - Olga Stroganova; Svyatoslava Bozhik; Larisa Voronova; Natalia Antoshkova (MDPI AG, 2019)
Recent studies have shown that the number of international students, who are academically mobile, is growing. As a result, higher education institutions aim at competitiveness in the world market. Therefore, the core issue of the following work is a process of adaptation of international students to a new educational environment, especially to the process of English teaching and learning in new frameworks. Thus, the purpose of the study is to understand the role of a language teacher in the process of international students’ foreign language learning by comparing faculty’s and students’ views on certain aspects of the educational process. For the following study, quantitative and qualitative methods to collect data using questionnaires with closed-ended and open-ended questions were applied, and the data analysis was carried out. The data obtained from the conducted survey reveals the importance of studying English for international students, their motivation and difficulties that they have to face. Moreover, the obtained data show the great complexity of the English syllabus and ways of its adaptation to the needs of international students. Furthermore, the results of the survey determine an important role of the professional culture of the second language teacher in the context of integrating students into the Russian academic environment.